Improving Students’ Translation Mastery by Hypnoteaching Implementation - Juwita Boneka Sinaga (English Department, University of Riau Kepulauan, Batam,Indonesia, 2016)
There is a need to know why students feel so nervous and lack of confidence when speaking. There may be a relationship between their metacognitive strategy and their self-efficacy in speaking skill. This research aimed at improving students’ translation mastery by hypnoteaching implementation. Hypnoteaching stands for two words- hypnosis and teaching. Majid defines hypnosis as a condition like a sleep called trance due to the reduction of brain wave from beta to alpha or theta. In this condition, the client’s conscious mind is opened and the hypnotist can give suggestions directly to the subconscious mind. This research was a quantitative research classified into a true experimental design. In this research, the instrument that used was multiple choice consist of 10 items. The researcher used t-test formula to find out whether there was a significant difference between the both classes after being treated. Based on the findings on the discussion, the researcher concluded that the implementation of Hypnoteaching method effectively improves the second year students’ translation ability at SMA Negeri 6 Padangsidimpuan, Bone. It could be proven by looking at the comparison between the T-test value and T-table value. The T-test value is 5.957 and with 1% of significance level and 38 degree of freedom, T-table value is 2.712 because the T-test value is higher than T-table, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. That significant improvement could be observed in the students’ motivation while the learning process runs.Keywords: translation mastery, hypnoteaching